Weighing simulated galaxy clusters using lensing and X-ray - Meneghetti, Massimo; Rasia, E.; Merten, Julian; Bellagamba, F.; Ettori, S.; Mazzotta, P.; Dolag, K.; Marri, S. (Astronomy and astrophysics, 2010)
Context. Among the methods employed to measure the mass of galaxy clusters, the techniques based on lensing and X-ray analyses are perhaps the most widely used; however, the comparison between these mass estimates is often difficult and, in several clusters, the results apparently inconsistent.Aims. We aim at investigating potential biases in lensing and X-ray methods to measure the cluster mass profiles.Methods. We performed realistic simulations of lensing and X-ray observations that were subsequently analyzed using observational techniques. The resulting mass estimates were compared with the input models. Three clusters obtained from state-of-the-art hydrodynamical simulations, each of which projected along three independent lines-of-sight, were used for this analysis.Results. We find that strong lensing models can be trusted over a limited region around the cluster core. Extrapolating the strong lensing mass models to outside the Einstein ring can lead to significant biases in the mass estimates, if the BCG is not modeled properly, for example. Weak-lensing mass measurements can be strongly affected by substructures, depending on the method implemented to convert the shear into a mass estimate. Using nonparametric methods which combine weak and strong lensing data, the projected masses within R200 can be constrained with a precision of ~10%. Deprojection of lensing masses increases the scatter around the true masses by more than a factor of two because of cluster triaxiality. X-ray mass measurements have much smaller scatter (about a factor of two less than the lensing masses), but they are generally biased toward low values between 5 and 10%. This bias is entirely ascribable to bulk motions in the gas of our simulated clusters. Using the lensing and the X-ray masses as proxies for the true and the hydrostatic equilibrium masses of the simulated clusters and by averaging over the cluster sample, we are able to measure the lack of hydrostatic equilibrium in the systems we have investigated.Conclusions. Although the comparison between lensing and X-ray masses may be difficult in individual systems due to triaxiality and substructures, using a large number of clusters with both lensing and X-ray observations may lead to important information about their gas physics and allow use of lensing masses to calibrate the X-ray scaling relations.
Gesehen am 14.04.2023